Pengaruh Kebijakan Pengelolaan Aset Daerah Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Provinsi Jawa Barat - Anisya Luthfiani; Drs. Sudjana M.Si.Ak (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The management of regional assets has become a critical component of a region's ability to produce a solid Regional Financial Report. This study was done to see how regional asset management can affect a regional government's financial report. The management of regional assets has become a critical component of a region's ability to produce a solid Regional Financial Report. This study was done to see how regional asset management can affect a regional government's financial report. Furthermore, this study technique entails conducting a field survey and documenting asset management policies used by the Regional Government of West Java Province in the administration of regional assets. The findings of this study show that regional asset management strategies have a favorable and significant impact on the quality of financial reporting. This, the expected results of this study is to assist regional government in making a policy in making decisions on the management of regional assets.